108th AES Convention, Paris - 19 – 22 February, 2000 - SANKIEWICZ, Marianna (Archives of Acoustics, 2000)
Polish participation in the AES Conventions has already become a well founded tradition. So it was this year also, at an exceptional place and date — Paris 2000. The 108th Convention was the first in the French capital for five years. It was held at the newly refurbished Palais des Congres (see photo of a group of Polish participants before the Palais front), which played host to over three hundred exhibitors’ booths from all over the world; among them all leading enterprises in the field of sound and vision techniques.